Implementation of Simultaneous Regional Elections during the Covid-19 Pandemic from Qawaid Fiqhiyyah's Perspective - Hairuman, Bambang; A`isyah, Siti (AL-WIJDÃN Journal of Islamic Education Studies, 2025)
This research analyzes the implementation of simultaneous Regional Head Elections (Pilkada) during the COVID-19 pandemic from a qawaid fiqhiyyah perspective. This research method is an analytical approach to Islamic law, using qawaid fiqhiyyah as a basis for analyzing the implementation of simultaneous regional elections during the pandemic. The results of this research are as follows: First, Maqasid al-Syariah (objects of sharia). In the context of simultaneous regional elections during a pandemic, this perspective helps determine the most appropriate actions to maintain public safety and health as the main goal. Second, dharurat (emergency). These principles help interpret religious law and provide flexibility in dealing with emergencies such as the COVID-19 pandemic. Third, the principle of public interest. In the context of simultaneous regional elections during the pandemic, this is used as the basis for decision-making regarding implementing elections. Fourth, Hifdz al-Aql (mind protection). In the context of simultaneous regional elections during a pandemic, this principle can encourage rational action and minimize the risk of spreading the virus. Fifth, human glory honor, and dignity. In this context, individual rights must be respected and the protection of their health must be prioritized. Keywords: Pilkada, Covid-19, Qawaid Fiqhiyyah